2008
DOI: 10.1007/s00018-008-8525-0
|View full text |Cite
|
Sign up to set email alerts
|

HCN channels: Structure, cellular regulation and physiological function

Abstract: Hyperpolarization-activated and cyclic nucleotide-gated (HCN) channels belong to the superfamily of voltage-gated pore loop channels. HCN channels are unique among vertebrate voltage-gated ion channels, in that they have a reverse voltage-dependence that leads to activation upon hyperpolarization. In addition, voltage-dependent opening of these channels is directly regulated by the binding of cAMP. HCN channels are encoded by four genes (HCN1-4) and are widely expressed throughout the heart and the central ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
401
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 372 publications
(417 citation statements)
references
References 245 publications
(273 reference statements)
13
401
2
1
Order By: Relevance
“…In dendrites, modifying the HCN channel alone had little effect on SKF83959-regulated neuronal excitability, which may be the result of a balance between excitatory and inhibitory effects. The difference between the responses of the soma and dendrites was most likely due to the much higher density of HCN channels in dendrites than in soma [27,37] . Moreover, we found that modifying the Na + channel or kdr channel alone facilitated depolarization block, consistent with previous studies [31] .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In dendrites, modifying the HCN channel alone had little effect on SKF83959-regulated neuronal excitability, which may be the result of a balance between excitatory and inhibitory effects. The difference between the responses of the soma and dendrites was most likely due to the much higher density of HCN channels in dendrites than in soma [27,37] . Moreover, we found that modifying the Na + channel or kdr channel alone facilitated depolarization block, consistent with previous studies [31] .…”
Section: Discussionmentioning
confidence: 99%
“…However, the specific role of HCN channels in SKF83959-regulated neuronal excitability is rather complex. It has been reported that the HCN channel can produce either excitatory (depolarizing the membrane) or inhibitory (decreasing the input resistance) effects on the excitability of pyramidal neurons [25][26][27][28] . In previous studies, the excitability of these neurons has been measured with the depolarized membrane potential compensated to the control level, which in some respects resulted in selectively neglecting the excitatory effect.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations